PEMBELAJARAN GASING BERBASIS MULTIPLE INTELLIGENCE UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR PESERTA DIDIK SMP - Poppy Kurnia Lestari; Haratua Tiur Maria; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research aimed to determine the implementation of Multiple Intelligence-based GASING learning to improve student learning outcomes and interest in straight motion material in Junior High School 1 Sungai Ambawang. This research used experiment method with  pre-experimental design form and one group pretest-posttest model design. The data sources of this research included students of class VIII by analyzed their answers’ form of learning interests and learning outcomes before and after implemented Multiple Intelligence-based GASING learning. The results showed an increase in learning interest of 55.20% with the effectiveness of increased interest gained from the normalised gain value to illustrate how well the influence of the learning implementation is relatively high for. Wilcoxon Signed Rank Test revealed a significant increase in students' learning outcomes showed by (Asymp.Sig. (2-tailed) = 0,000 < 0,05), with the effectiveness of increased learning outcomes based on normalised gain value is pretty moderate  Based on these results, it can be concluded that Multiple Intelligence-based GASING learning effective in improving students ' learning outcomes and interests. The researcher hopes this learning will be used as an alternative teaching physics learning to enhance student learning outcomes and interest. Keywords: GASING, Learning Interest, Learning Outcome, Multiple Intelligence